Effects of continuous‐flow left ventricular assist devices on cerebral hemodynamics. Issue 5 (9th January 2020) - Karahan, Mehmet; Kocabeyoglu, Sinan Sabit; Kervan, Umit; Sert, Dogan Emre; Aygun, Emre; Tola, Muharrem; Demirkan, Burcu; Mungan, Semra; Kursun, Oguzhan; Catav, Zeki; Pac, Mustafa
Abstract: Continuous‐flow left ventricular assist devices (LVADs) reduce peak systolic flow, increase diastolic flow, and eliminate pulsatility of circulation. Altered blood flow may lead to a change in end‐organ perfusion. Analysis of the flow dynamics of the arteries of end organs, such as the brain, may indicate whether an organ is perfused sufficiently. The aim of this study is to evaluate and identify the flow pattern changes of carotid (CA) and middle cerebral arteries (MCA) in LVAD patients and to compare with heart failure patients and healthy volunteers. Eighty‐nine individuals were included in this cross‐sectional study. Participants were divided into three groups: LVAD patients ( n = 31), heart failure patients ( n = 26), and healthy volunteers ( n = 27). Carotid and transcranial Doppler ultrasonography were performed for all study groups for peak systolic velocity (PSV), end‐diastolic velocity (EDV), pulsatility (PI), and resistive (RI) indices of CA and MCA. Flow dynamics were compared between the groups. Doppler ultrasonographic data were analyzed at a median 12 (3‐47) months after LVAD implantation. CA‐PSV was lower in LVAD group compared with the other two groups ( P < .001), MCA‐PSV of LVAD and heart failure groups were similar and lower than healthy volunteers ( P < .05). The highest values for CA‐EDV were found in the LVAD group ( P < .05). MCA‐EDV values were found to be lowest in heart failure group ( P < .05). For PI and RI, in all CA and MCA, the LVAD group had lower indices compared with the other two groups ( P < .001). In addition, MCA flow analysis in patients with LVADs was identified for the first time with this study.